Spatial patterning of the archaeological and paleontological assemblage at Dmanisi, Georgia: An analysis of site formation and carnivore-hominin interaction in Block 2. Issue 143 (June 2020) - Coil, Reed; Tappen, Martha; Ferring, Reid; Bukhsianidze, Maia; Nioradze, Medea; Lordkipanidze, David
Abstract: This study addresses the roles of biotic agents in site formation in the B1 strata of Block 2 at Dmanisi, Georgia, using theoretical and analogous frameworks for the interpretation of spatial behaviors of carnivores and hominins. For this study, stone material, faunal remains, and coprolites are analyzed to determine if any spatially distinct behaviors can be identified, located, and attributed to either hominins or carnivores. Faunal, stone, and coprolite assemblages are compared with each other, and lithic, taxonomic, and taphonomic subassemblages are compared with the overall distribution of their parent material. The spatial and taphonomic signatures suggest that hominin activity was only a small part of the contributing factors to site formation, whereas carnivores played a major role in the accumulation of bone.